Analysis Of Performance Of Beef Sub-Sector In Peninsular Malaysia - Hosseini Matin, Anahita (2009)
Food production is not keeping pace with food demand. Growth in food production is consistently falling behind population growth making food shortages a recurrent problem. On the other hand, global financial crisis necessitates that world countries reach certain level of self-sufficiency in producing basic commodities. In Malaysia, the production of fresh beef is not enough to answer the people’s need, either as food security reasons or to increase self-sufficiency level for the country. The major problem is that the beef sub sector of Malaysia has remained uncommercialized due to low productivity and the private sector has been silent on the beef sub sector development. The objectives of this study is to develop a Model for beef policy analysis in order to investigate the future trend of beef self sufficiency level in Malaysia via biological and mathematical simulation beef model, to develop a beef production system modeling for policy analysis, to predict the beef supply trend in future plans, and to analyze the benefit/cost of implementing alternative policy in increasing beef production in Malaysia. Vintage approach simulation matrix model (VASIMM) was used to analyze the objectives of the study. The VASIMM method uses aggregate data on bringing the new breeding stock into the model, reproduction of existing breeding stocks, and culling rate, to derive a theoretical slaughter system based on different rates of calving, replacement, mortality, and slaughter in the past, as reduction rates to system simulation, and simulate the final results of female breeding stocks, male breeding stocks, female calves, male calves, slaughter, and production of beef cattle, dairy cattle, and buffalo. The ex-post simulation analysis was applied for 1960-2006 period, and the model was validated using RMSE, RMSPE, and U-Theil inequality coefficient, as the base model of ex-ante simulation model. The ex-ante simulation analysis was developed by examining different policy variables, such as mortality, slaughter, and calving rate, importation of female breeding stocks, and importation of animal for slaughter, in 9 different Scenarios. Scenario 1 depicts the current situation of fresh beef production in Malaysia without any breeding stock importation. Scenario 2 assumes that all management variables (mortality rate, slaughter rate, etc) are the same as in Scenario 1, but there are 10,000 heads of female breeding stock importation. In Scenario 3, apart from the importation of female breeding stock, the management is also improved. Scenario 4 investigates the poor management system of the industry while Scenario 5 analyzes the effects of importing 10,000 heads of beef cattle and buffalo for slaughter under the current situation. Scenarios 6, 7, and 8 are similar to Scenarios 2, 3, and 4 respectively, but the importation of beef cattle and buffalo for slaughter is added to each of them. Lastly, Scenario 9 investigates what changes in the current situation of fresh beef production would be if 50,000 heads of female breeding stock are imported in 2010, 2011, and 2012. Amongst these 9 Scenarios, only Scenario 3 is economically applicable in long run, and can fulfill the targeted level of self-sufficiency (40%) by 2020. The results of positive Net Present Worth (NPW) and 45% level of self sufficiency under the following conditions of 3-4% mortality rate, 5-10% slaughter rate, 75-78% calving rate, importation of 10,000 heads Beef cattle, 500 heads Dairy cattle, and 500 heads Buffalo female breeding stock/year by 2010, respectively, indicate that under Scenario 3, in long run Malaysia can be independent on fresh beef importation. While, the negative value of NPW and low level of self sufficiency in Scenario 1, 2 , 4, 5, and 8 makes these Scenarios inapplicable. In Scenarios 6, 7 and 9, although the level of self sufficiency in beef production will be reached to the target and even exceed the target, the negative value of NPW depicts that Scenario 6, 7 and 9 are not economically feasible. The simulated results indicate that Malaysia can boost its fresh beef production by increasing importation of female breeding stock, and improving the management system by reducing the rate of mortality and slaughter, and increasing the rate of calving, so that Malaysia would be independent on beef production in the near future.